2017
DOI: 10.4018/978-1-5225-2084-9.ch021
|View full text |Cite
|
Sign up to set email alerts
|

Value Co-Creation in Fitness Centers

Abstract: The purposes of this chapter were (1) to identify the role of customer citizenship behavior (CCB) in value co-creation and (2) to examine the relationships among CCB, perceived value, satisfaction, and repurchase intention of customers in the context of fitness centers. Data were collected from customers at commercial fitness clubs in the region of Greater Taipei. The results showed that CCB has a positive influence on perceived value and satisfaction, which in turn have positive influences on repurchase inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…First, this study found that service encounters had a positive impact on perceived value (H2), which in turn affected repurchase intention (H3). These findings are consistent with previous studies (Chiu et al. , 2017; Rather et al.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…First, this study found that service encounters had a positive impact on perceived value (H2), which in turn affected repurchase intention (H3). These findings are consistent with previous studies (Chiu et al. , 2017; Rather et al.…”
Section: Discussionsupporting
confidence: 94%
“…It implies that the impact of service encounter on repurchase is not a simple input-output relationship and that this relationship is mediated by the relative level of customers' perceived value. It is noteworthy that fitness services emphasize the direct interaction between people (Chiu et al. , 2017; Woratschek et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations